Anthropometric and Physiological Profile of Mixed Martial Art Athletes: A Brief Review - Charalampos Spanias; Pantelis T. Nikolaidis; Thomas Rosemann; Beat Knechtle (MDPI AG, 2019)
The aim of this review was to analyze the existing knowledge of the anthropometric and physiological characteristics of MMA (mixed martial arts). A computerized search was performed in the PubMed and Google Scholar databases for English-language, peer-reviewed investigations using the term “mixed martial arts” or “MMA” alone and in combination with “physiological characteristics”, “physiological profile”, “body composition”, “strength”, “power”, “endurance”, “aerobic”, and “anaerobic”. The main findings of this review suggested an overall profile of low body fat, high flexibility, muscle strength, muscle endurance, and anaerobic power, and average cardiovascular endurance. Nevertheless, no differences in anthropometric and physiological characteristics by performance level of the athletes were observed. Based on the studies analyzed in this review, several limitations were reported. First, the subjects in each paper were limited in number, as is MMA literature itself, and it is impossible to make a generalization regarding the anthropometric and physiological profile for male athletes. Second, no studies included female MMA athletes; therefore, there was no evidence for what their profiles might be. Last, the majority of the above-mentioned studies used different tests, or the same tests with different protocols, and as a result, it is difficult to compare their results. The similarity observed between the levels of the athletes might be a result of the different tests and protocols used by the researchers or might be evidence that the anthropometric and physiological profile of an MMA athlete did not vary among high-level athletes. Considering the increasing number of those engaging in MMA training and sport events, the findings of the present study provided strength and conditioning trainers working with MMA athletes a valuable tool for monitoring training and performance.